Vaccinium orthocalyx (Ericaceae), a new species from Xizang, China with taxonomic notes on V. arbutoides and V. brachyandrum - Xu, Hong-Yan; Guo, Yong-Jie; Cai, Jie; Tong, Yi-Hua; Armstrong, Kate E. (Phytotaxa, 2026)
A new species of Vaccinium (Ericaceae), V. orthocalyx, from Xizang Autonomous Region, China, is described and illustrated. This new species is morphologically similar to V. brachyandrum and V. usneoides, but differs from the former by its shorter petioles, lateral veins flat or slightly raised adaxially and inconspicuous abaxially, tertiary veins inconspicuous on both sides, and red corolla, and from the latter by its much larger leaf blades, more pairs of lateral veins, glabrous to subglabrous hypanthium and filaments, and longer pedicels. The floral morphology of V. arbutoides is described for the first time based on living plant photos and dried specimens. The new record of V. brachyandrum in Myanmar is also reported. Colour plates and taxonomic notes of these species are provided in this study.